Unmanned aircraft systems roadmap to the future - Toscano, Michael (Kansas State University, 2014)
AUVSI’s mission is to advance the unmanned systems and robotics community through education, advocacy and leadership. AUVSI’s vision is to improve humanity by enabling the global use of robotic technology in everyday lives. In its 41st year, AUVSI is the world’s largest non-profit association devoted exclusively to unmanned systems and robotics. AUVSI represents more than 7,500 members, including more than 600 corporate members from more than 60 allied countries.
Keywords: Association for Unmanned Vehicle Systems International; Unmanned air vehicles; Industry; Economics; Legislation